A comparison of the performance of 2.5 to 3.5-year-old children without disabilities using animated and cursor-based scanning in a contextual scene. Issue 4 (8th August 2018) - McCarthy, John W.; Boster, Jamie B.
ABSTRACT: Although recent evidence suggests learning demands for children can be reduced by organizing augmentative and alternative communication (AAC) displays in contextual scenes, there is little evidence on how such scenes could be made accessible for children who cannot use direct selection. Using a line drawn scene of a living room, a traditional traveling cursor (a green outline of objects within the scene) was compared with sequential animation—logically matching the function of items in the scene (e.g., hands of a clock moving, a lamp turning on and off, etc.). After three learning sessions, only the matched function animation condition revealed a significant increase in accuracy scores from session 1 to session 3. Age-related trends suggested the mean scores in the cursor-based condition were associated with older children consistently performing at high levels and younger children remaining at low levels, while trends in the animated group were associated with children learning the interface in a way not associated with age. Findings support that enhanced presentations of scanning can increase the transparency of the scanning interface for some children and suggest that contextual scene displays could benefit from animations and sound for children not using direct selection.